Pemodelan Tingkat Kebisingan Lalulintas di Lingkungan Perumahan(Studi Kasus: Perumahan Dosen UGM â Sekip Yogyakarta). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Traffic noise levels at residential areas varied depending on many variables. Many researchers investigated noise levels near the road edge. This research aimed at investigating traffic noise levels at many receiving points at a residential area as well as modeling the noise levels based on many variables such as traffic factors, road factors and environmental factors. The data were collected by direct measurement. The noise index used was energy mean noise level, Ley. The model was developed using statistical methods. The results indicated that noise levels occurring in the area exceeded the noise level standard, that were, between 71.89 a(A)-75.64dB(A). compared to 55 dB (A). It was found that traffic noise levels were determined mainly by traffic .flows and speeds, distances, but not by traffic composition.